Genetic Manipulation of Competition for Nitrate between Heterotrophic Bacteria and Diatoms - Diner, Rachel E.; Schwenck, Sarah M.; McCrow, John P.; Zheng, Hong; Allen, Andrew E. (Frontiers in Microbiology, 2016)
Diatoms are a dominant group of eukaryotic phytoplankton that contribute substantially to global primary production and the cycling of important elements such as carbon and nitrogen. Heterotrophic bacteria, including members of the gammaproteobacteria, are commonly associated with diatom populations and may rely on them for organic carbon while potentially competing with them for other essential nutrients. Considering that bacterioplankton drive oceanic release of CO2 (i.e., bacterial respiration) while diatoms drive ocean carbon sequestration vial the biological pump, the outcome of such competition could influence the direction and magnitude of carbon flux in the upper ocean. Nitrate availability is commonly a determining factor for the growth of diatom populations, particularly in coastal and upwelling regions. Diatoms as well as many bacterial species can utilize nitrate, however the ability of bacteria to compete for nitrate may be hindered by carbon limitation. Here we have developed a genetically tractable model system using the pennate diatom Phaeodactylum tricornutum and the widespread heterotrophic bacteria Alteromonas macleodii to examine carbon-nitrogen dynamics. While subsisting solely on P. tricornutum derived carbon, A. macleodii does not appear to be an effective competitor for nitrate, and may in fact benefit the diatom; particularly in stationary phase. However, allochthonous dissolved organic carbon addition in the form of pyruvate triggers A. macleodii proliferation and nitrate uptake, leading to reduced P. tricornutum growth. Nitrate reductase deficient mutants of A. macleodii (ΔnasA) do not exhibit such explosive growth and associated competitive ability in response to allochthonous carbon when nitrate is the sole nitrogen source, but could survive by utilizing solely P. tricornutum-derived nitrogen. Furthermore, allocthonous carbon addition enables wild-type A. macleodii to rescue nitrate reductase deficient P. tricornutum populations from nitrogen starvation, and RNA-seq transcriptomic evidence supports nitrogen-based interactions between diatoms and bacteria at the molecular level. This study provides key insights into the roles of carbon and nitrogen in phytoplankton-bacteria dynamics and lays the foundation for developing a mechanistic understanding of these interactions using co-culturing and genetic manipulation.